Fiber-optic technologies for real-time monitoring of coastal landslides: a review of their role in early warning systems - Cemiloglu, Ahmed; Chengyong, Jin; Teng, Fei; Nanehkaran, Yaser A.; Raoof, Amir; Sweijen, Thomas; Derakhshani, Reza (Frontiers in Earth Science, 2025)
Effective early warning systems are crucial for mitigating the risks of landslides in vulnerable coastal areas. With the increasing frequency of coastal landslides, precise monitoring solutions are essential for timely interventions. This review addresses real-time monitoring by fiber-optic technologies, which offer high precision, rapid data acquisition, and adaptability, making them a promising solution. Fiber-optics provide continuous, real-time data for early detection of ground movements, unlike traditional methods that struggle with spatial and temporal coverage. Fiber-optic sensors cover large areas and maintain a high frequency, allowing for a detailed assessment of landslide behavior. This review highlights successful implementations of fiber-optic monitoring in both lab and field settings, showcasing their versatility and effectiveness. This review demonstrates the significant contributions of fiber-optic technologies in improving landslide monitoring and risk management. By enabling timely and accurate data collection, these sensors enhance early warning systems and trigger proactive responses to protect lives and infrastructure. Additionally, their use aids in understanding landslides, developing effective mitigation strategies, and land use planning, ultimately strengthening the resilience 22 of coastal communities.